Analysis of Variation in Foreign Inflows by Different Categories of Foreign Portfolio Investors - Gupta, Akriti; Kumar, Parul (Indian economic journal, 2024)
The liberalisation of Indian financial markets has smoothened the capital flows of international institutional investors, resulting in rising foreign investor participation in the domestic equity and debt markets. Since the reforms of the 1990s, India has become one of the favourite investment hubs of foreign institutional investors (FIIs) across the globe. The research aims to analyse the variation in contribution to foreign inflows by the three different categories of foreign portfolio investments (FPIs) and the determinants of inflows of the categories of FPIs. The study is based on the use of secondary data collected from the National Securities Depository Limited and the Securities Exchange Board of India. One-way ANOVA has been employed to examine the variation in inflows by different categories of FIIs. Autor regressive distributed lag model has been used to understand the factors determining the inflows of FPIs. The results of the study revealed that there exists variation in the inflows of investments among the different categories of FIIs. The variation in inflows by different categories into equity instruments was significant, while the inflows into debt instruments were not significant. Furthermore, the highest inflows were seen from the second category of FIIs. JEL Codes: C32, G2